Linux : the textbook - Sarwar, Syed Mansoor; Koretsky, Robert (Boca Raton, FL : Taylor & Francis, CRC Press, 2019)
Linux: The Textbook, Second Edition provides comprehensive coverage of the contemporary use of the Linux operating system for every level of student or practitioner, from beginners to advanced users. The text clearly illustrates system-specific commands and features using Debian-family Debian, Ubuntu, and Linux Mint, and RHEL-family CentOS, and stresses universal commands and features that are critical to all Linux distributions. The second edition of the book includes extensive updates and new chapters on system administration for desktop, stand-alone PCs, and server-class computers; API for system programming, including thread programming with pthreads; virtualization methodologies; and an extensive tutorial on systemd service management. Brand new online content on the CRC Press website includes an instructor's workbook, test bank, and In-Chapter exercise solutions, as well as full downloadable chapters on Python Version 3.5 programming, ZFS, TC shell programming, advanced system programming, and more. An author-hosted GitHub website also features updates, further references, and errata. FeaturesNew or updated coverage of file system, sorting, regular expressions, directory and file searching, file compression and encryption, shell scripting, system programming, client-server-based network programming, thread programming with pthreads, and system administration Extensive in-text pedagogy, including chapter objectives, student projects, and basic and advanced student exercises for every chapter Expansive electronic downloads offer advanced content on Python, ZFS, TC shell scripting, advanced system programming, internetworking with Linux TCP/IP, and many more topics, all featured on the CRC Press website Downloadable test bank, work book, and solutions available for instructors on the CRC Press website Author-maintained GitHub repository provides other resources, such as live links to further references, updates, and errata.
1. Overview of Operating Systems2. "Quick Start" into the Linux Operating System3. Editing Text Files4. Files and File System Structure5. File Security6. Basic File Processing 7. Advanced File Processing8. File Sharing9. Redirection and Piping10. Processes11. Networking and Internetworking12. Introductory Bash Programming13. Advanced Bash Programming14. Linux Tools for Software Development15. System Programming I: File System Management16. System Programming II: Process Management and Signal Processing17. Linux System Administration Fundamentals18. SystemdAppendix A: Installation InstructionsAppendix B: Books for Further ReferenceGlossaryIndex
Includes index.
CSE
Parama
Keywords: Linux; Operating systems (Computers).; Computer science